Characterization and molecular identification of bacteria from mackerel bekasam in Sorong City, Southwest Papua Province, Indonesia - SUKMAWATI SUKMAWATI; RATNA RATNA; SIPRIYADI SIPRIYADI; MELDA YUNITA (Society for Indonesian Biodiversity, 2023)
Abstract. Sukmawati S, Ratna R, Sipriyadi, Yunita M. 2023. Characterization and molecular identification of bacteria from mackerel bekasam in Sorong City, Southwest Papua Province, Indonesia. Biodiversitas 24: 4967-4977. Bekasam is traditional food type produced by traditional fermented fish. Microbes that grow through fermentation play an important role in forming the product’s aroma, texture, and overall quality. The study aimed to determine the biochemical characteristic of bacteria from mackerel (Scomberomorus sp.) bekasam in Sorong City and identify bacteria at the molecular level. This research was a descriptive study, which described the results of the characterization of bacteria from fermented mackerel fish and the results of molecular identification to the species level through the PCR (Polymerase Chain Reaction) technique. Then, the DNA sequences were further analyzed using the agarose gel electrophoretic separation method to visualize the bacterial DNA profile. The biochemical characterization of bacterial isolates from mackerel showed that all isolates were negative indole, and eight isolates were positive in reducing nitrate. In comparison, four isolates were negative in reducing nitrate, then all isolates had proteolytic activity except the FST 3.1 and FST 3.2 isolates. Eleven isolates were positive in hydrolyzing fat, and one isolate could not hydrolyze fat. According to the DNA patterns seen in electrophoresis and alignment of the 16 sRNA gene sequences, several types of bacteria had been identified as Bacillus paramycoides strain 2883 FST 1.1, Bacillus paramycoides strain 3665 FST 2.1, Bacillus mobilis strain ICA-144 FST 3.1, Bacillus cereus strain ATCC 14579 FNT 1.1, Bacillus mobilis strain ICA-144 FNT 2.1, and Bacillus cereus strain ATCC 14579 FNT 3.1.